Epidemiology of Bruxism and Temporomandibular Joint Disorders (TMD) in Iranian Adults: A Cross-Sectional Study - Amini, Parviz; Sharifi, Maryam; Aftabi, Reyhane; Jahanimoghadam, Fatemeh; Jahanimoghadam, Hamidreza (Journal of Dentistry Indonesia, 2024)
Objective: The prevalence of bruxism in the literature has been reported differently. The aim of this study was to assess the prevalence of bruxism in patients aged 25–40 who were referred to Kerman Dental School. Methods: This analytical descriptive cross-sectional study was performed on 320 patients referred to the Department of Oral Medicine of Kerman Dentistry Faculty in the age range of 25 to 40 years old. The prevalence of bruxism as well as TMJ disorders were evaluated. Data were collected in a questionnaire and entered into SPSS version 24. Analyzing was done by a chi-square test at a significant level of 0.05. Results: The prevalence of bruxism was 23.8%, with superiority in women. Although clenching was observed in 95.5% of the patients, 84.4% showed premature contacts on teeth, most of them related to the non-working side, and 82.9% presented premature contacts on restorations, especially on the non-working side. Regarding TMD symptoms, pain was the most common (83.4%), and clicking and crepitus were seen in 42% and 6% of the patients, respectively. Also, in 63.7% of the subjects with bruxism, jaw deviation was observed, and 18.7% showed restricted jaw movement. Conclusion: The prevalence of bruxism in the studied population is in the range of similar studies. Regarding TMD, troublesome symptoms such as pain, jaw deviation, and limited mouth opening were the only ones significantly related to bruxism.